Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Siswa pada Materi Sel di Kelas XI MIA SMA Negeri 1 Masama - Nurlia, Nurlia (Universitas Sulawesi Barat, 2023)
One learning approach that emphasizes the achievement of learning outcomes is Problem-Based Learning (PBL). Problem-based learning (PBL) requires students' active involvement in the learning context, not just relying on instructions from the teacher. Thus, Problem-Based Learning (PBL) stimulates the growth of a strong mindset in students, this suggests that applying a problem-solving-orientated learning model can improve student learning achievement. The purpose of this study was to determine the effect of the Problem-Based Learning (PBL) learning model on student learning outcomes on cell material in class XI MIA SMA Negeri 1 Masama. This study used a pseudo-experimental method and quantitative data-based research. The population was all students in class XI MIA at SMA Negeri 1 Masama. The research sample consisted of two classes, namely class XI MIA 1 with 25 students and class XI MIA 2 with 24 students. Thus, the total number of samples used was 49 students. Data collection techniques through the test method contained multiple choice questions used in the pre-test and post-test. Data were analyzed using descriptive analysis techniques and hypothesis testing. The results showed that the use of the Problem-Based Learning (PBL) learning model influenced student learning outcomes in class XI MIA SMA Negeri 1 Masama, with a significance value of α = 0.000 <0.05.